Character Design for Educational Games â€œCaring for The Urban Forest in Jakartaâ€ - Tunjung Riyadi (Bina Nusantara University, 2017)
The existence of the urban forest in Jakarta become a valuable asset for its residents. Unfortunately, the urban forest less aware of its existence. This unconsciousness due to lack of information about the existence of the urban forest itself. The design aims to create unique and attractive character, which helps inform the existence of the urban forest in Jakarta, through educational games. The design method through the stages of observation in the form of visual data search, analysis elaboration mapping problem, then visually determining the essential character as the main idea. The result is a character design with the function as the